Kobeko Learning Model based Web Blog (High education ballad amid the siege of Covid-19): Model Pembelajaran Kobeko Berbasis Web Blog (Balada Pendidikan Tinggi di Tengah Kepungan Wabah Covid-19) - Siti Osa Kosassy (International Journal of Technology Vocational Education and Training, 2020)
One of the hot topics that continues to be discussed today is the change in the learning process where from face to face in school to "learning from home". This policy is a matter that certainly makes educators to aggressively train and get used to the changes that will occur. This study aims to map the needs of developing competency-based contextual learning models, producing competency-based contextual learning models that are valid, practical and effective. Reveal the level of validity and practicality of competency-based contextual learning models. Disclose the level of effectiveness of competency-based contextual learning models on student abilities. This type of research is research and development (R&D) using the ADDIE model. The results of this study indicate that the blog-based Kobeko learning model is able to improve the critical abilities and activeness of students and the implementation of the web-based Kobeko learning model blog has several stages. The implementation model starts from the formulation, the apperception stage to students, the exploration stage, where educators provide information about the outline of the material. The implementation of the web-based Kobeko learning model is the evaluation stage. The evaluation phase is carried out by educators and also students.